Research on fractional repetition codes based on group divisible designs - Bing ZHU; Hui LI; Jun CHEN; Han-xu HOU; Tai ZHOU (Tongxin xuebao)
A novel design of FR (fractional repetition) codes was proposed which aims at providing efficient repair at the minimum bandwidth regenerating point.The design consisted of an outer MDS (maximum distance separable) code and an inner repetition code,called GDDBFR (group divisible design based FR) codes.The proposed codes can achieve the system storage capacity under the random access model and are available for a wide range of parameters.Despite of the table-based repair,theoretical analysis identifies that GDDBFR codes generally have large node repair alternatives.Furthermore,experimental results show that GDDBFR codes can significantly reduce the failure repair time when compared with legacy RS (Reed-Solomon) codes and regenerating codes in the domain.